Comparative Analysis of the Systems of Recognition and Enforcement of Foreign Judgments Pursuant to the Serbian Law on Resolution of Conflicts of Laws with Provisions of Other Countries and the 2019 Hague Judgments Convention - Jovanović, Marko; Marjanovic, Sanja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
Slightly more than a year ago, the Convention on Recognition and Enforcement of Foreign Judgments in Civil and Commercial Matters has entered into force. That Convention was adopted in July 2019 under the auspices of the Hague Conference on Private International Law. Seeing its drafting history, the quality of its solutions and the ambitions of its most vocal proponents, it is likely to expect that the Convention will become one of the most important sources of private international law in future. In light of the potential need for Serbia to join this Convention, it is useful to compare the rules on recognition contained in the domestic Law on Resolution of Conflicts of Laws with Provisions of Other Countries on the one side and the Convention on the other. The analyses show that, despite certain differences (mainly regarding the jurisdictional filters, the special rule on recognition of judgments awarding damages and the problem of recognition of a judgment in the matter where the proceedings in the requested State are still pending), there is no major divergence between the two systems. The differences noted can be explained by the differences in the nature between the two sources of law, as well as by the different times of their adoption. It should be particularly emphasized that the Convention contains a very sophisticated system of exclusions of some of its provisions from application. This can significantly ease the process of assessing the benefits of joining the Convention to all potentially interested States, including Serbia.